Effect of fortification of glycomacropeptides (GMP) on rheological and sensory attributes of probiotic-yoghurt - BP, pushpa; Heartwin, AP; Jayaprakasha, HM (Indian Journal of Dairy Science, 2022)
The objective of this study was to analyse the rheological and sensory attributes of glycomacropeptides (GMP) fortified probiotic-yoghurt prepared using Bifidobacterium bifidum (BB12) and Lactobacillus acidophilus (LA) cultures (1:1 ratio @ 4 %) in short set yoghurt. The textural properties of probiotic yoghurt fortified with GMP (0.25, 0.50 and 0.75 %) showed decreased firmness (N) and consistency (g.sec) whereas cohesiveness (N) and index of viscosity (g.sec) showed increased values with increasing levels of GMP addition. The apparent viscosity analysed using Brook Field Viscometer showed higher viscosity at 0.25 and 0.50 % GMP levels as compared to 0.75 % level and control. The sensory attributes of probiotic-yoghurt on 9 point Hedonic scale as evaluated by a panel of 7 judges, showed maximum scores for all the parameters (body and texture, flavour, sourness and overall acceptability) at 0.25 and 0.50 % levels of GMP. The current study demonstrated that statistically significant positive changes were observed in probiotic-yoghurt by fortification of GMP even at lower levels, with respect to rheological and sensory attributes.